1992
DOI: 10.1093/nar/20.4.719
|View full text |Cite
|
Sign up to set email alerts
|

Both fis-dependent and factor-independent upstream activation of the rrnB P1 promoter are face of the helix dependent

Abstract: Transcription from the Escherichia coli rrnB P1 promoter is increased by a cis-acting sequence which extends upstream of the -35 hexamer to about -150 with respect to the transcription initiation site, the Upstream Activation Region (UAR). Activation by the UAR involves two components: (1) a trans-acting protein, Fis, which binds to three sites in the UAR between -60 and -150, and (2) the UAR sequences themselves which affect RNA polymerase (RNAP) activity independent of other proteins. We refer to the latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 35 publications
9
85
0
Order By: Relevance
“…Nevertheless, many studies have demonstrated that altering the degree and/or phasing of upstream bending by introducing intrinsically bent DNA sequences (e.g., ref. 31) or by moving binding sites of activators (32) significantly increases (activates) or decreases (represses) the amount of transcription. Fig.…”
Section: Role Of Dna Bending and Upstream Wrapping In Transcription Amentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, many studies have demonstrated that altering the degree and/or phasing of upstream bending by introducing intrinsically bent DNA sequences (e.g., ref. 31) or by moving binding sites of activators (32) significantly increases (activates) or decreases (represses) the amount of transcription. Fig.…”
Section: Role Of Dna Bending and Upstream Wrapping In Transcription Amentioning
confidence: 99%
“…At 17°C, where the equilibrium constant K 1 is a maximum and conversion of I 1 to I 2 is relatively slow, we previously found that the fraction of promoter DNA in I 1 complexes ( I1 ) at 15 sec after mixing P R promoter with 70 nM (excess) RNAP was 0.55 (6). To increase the fraction of I 1 in the time interval (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (38) where the only complex predicted to be populated is I 1 (9). Because the signal:noise ratio in these 0°C experiments was marginal, and to avoid the possibility of populating off-pathway complexes at 0°C (39), we identified solution conditions where I 1 is Ͼ70% of promoter DNA (see above) at early times in the time course of RP o formation, and footprinted as follows.…”
Section: Determination Of Fractions Of Promoter Dna In I1 and Rpo Commentioning
confidence: 99%
“…The artificial upstream re-location of the rrnB P1 UP element by a single turn of DNA helix decreases but does not prevent transcription stimulation, while further displacements abolish UP elementdependent transcription (15). The ability of ␣CTD to contact DNA and/or activator molecules at different locations upstream of the core promoter (8,(15)(16)(17)(18)(19)(20)(21) has been attributed to the flexibility of the linker connecting ␣CTD to the ␣ amino-terminal domain (␣NTD) (8,22) assembled in the body of RNAP. This linker flexibility also accounts for the ability of the two copies of ␣CTD to function interchangeably with respect to the subsite recognition within the UP element (10).…”
mentioning
confidence: 99%
“…FIS Site I, the site closest to the promoter, accounts for 70 -80% of the effect of FIS on transcription (7). FIS most likely stimulates transcription by interacting directly with RNA polymerase (6,8, and A.J.Bokal, W.Ross, and R.L.Gourse, unpublished results).…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, if the A/T tracts are responsible for the small degree of curvature associated with this region, either the mutations do not affect this curvature, or the curvature plays little role in the 30-fold increase in transcription resulting from UP element function. On the other hand, either displacement of the UP element by non-integral portions of a helical turn (6,29,34) or creation of an additional T tract with a T substitution at position -37 (29,34) severely decreases promoter activity. Thus, correct positioning of the RNAP alpha subunit (which binds to the UP element) relative to the sigma subunit (which binds to the -10 and -35 hexamers) most likely plays a major role in promoter activity (2).…”
Section: Discussionmentioning
confidence: 99%